Development of learning design based on realistic mathematics education - Fitriana Fitriana; Edwin Musdi; Azwir Anhar (Fakultas Ilmu Pendidikan UNP)
The aim of this research is to develop the learning design based on Realistic Mathematics Education and to develop reasoning skills. The research design combines the Plomp model and the Gravemeijer and Cobb model, that consist of preliminary research phase, prototype development phase, preparation for the experiment, the implementation of the experiment, restrosfective analysis, and assessment phase. Data were collected through tests, interviews, observation, questionnaire and field notes. The subject of this research is VII grade student inislamic junior hight shcool 6 Piladang. The Learning design that was developed learning trajectory, that include learning objectives, activities, and prediction of students' answers implemented through the lesson plan and student worksheet. The result of this research produced a learning design which are valid, practical and effective. They are valid in terms of content and language, practical in terms of implementation, simplicity and required time.Effective in term of the impact of students’ mathematical reasoning skills.